Partial submission of Canada to the Commission on the Limits of the Continental Shelf regarding its continental shelf in the Atlantic Ocean.
On December 6, 2013 Canada filed a partial submission with the Commission on the Limits of the Continental Shelf in respect of its continental shelf in the Atlantic Ocean. Canada also filed preliminary information concerning the outer limits of its continental shelf in the Arctic Ocean. Canada is continuing to collect and analyze continental shelf data in the Arctic Ocean and is collaborating with neighbouring states in the scientific, technical and legal work needed to do so. Securing international recognition for the full extent of Canada’s extended continental shelf is a priority articulated in the Northern Strategy and the Statement on Arctic Foreign Policy.